2009
DOI: 10.1007/s10964-009-9418-8
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Educational Outcomes: Racial and Ethnic Variations in Peer Network Importance

Abstract: Little attention has been paid to the role of peer social capital in the school context, especially as a predictor of adolescents’ academic outcomes. This study uses a nationally representative (N = 13,738, female = 51%), longitudinal sample and multilevel models to examine how peer networks impact educational achievement and attainment. Results reveal that, in addition to those factors typically associated with academic outcomes (e.g., school composition), two individual-level peer network measures, SES and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…Combinations of PA and NA provide opportunities for the identification of cognitive-emotional pre-symptom profiles that underline individuals' pursuit of well-being (Archer, Adolfsson, & Karlsson, 2008;Archer, Adrianson, Plancak, & Karlsson, 2007;Nima, Archer, & Garcia, 2012). Recent analyses have focused upon the issue of ethnicity and affective states (Arango-Lasprilla et al, 2009;Le, Lai, & Wallen, 2009) as well as health status (Goza & Ryabov, 2009;Saalfrank, Wang, & Brown, 2009). It has been found that high levels of impulsive behavior are incompatible with positive affect and self-esteem but rather are associated with negative affect, external locus of control and amotivation (Archer, Kostrzewa, Palomo, & Beninger, 2010;Archer, Oscar-Berman, Blum, & Gold, 2012;Palomo, Beninger, Kostrzewa, & Archer, 2008a, b).…”
Section: Hypothesized Cultural Aspects: Main Effectsmentioning
confidence: 99%
“…Combinations of PA and NA provide opportunities for the identification of cognitive-emotional pre-symptom profiles that underline individuals' pursuit of well-being (Archer, Adolfsson, & Karlsson, 2008;Archer, Adrianson, Plancak, & Karlsson, 2007;Nima, Archer, & Garcia, 2012). Recent analyses have focused upon the issue of ethnicity and affective states (Arango-Lasprilla et al, 2009;Le, Lai, & Wallen, 2009) as well as health status (Goza & Ryabov, 2009;Saalfrank, Wang, & Brown, 2009). It has been found that high levels of impulsive behavior are incompatible with positive affect and self-esteem but rather are associated with negative affect, external locus of control and amotivation (Archer, Kostrzewa, Palomo, & Beninger, 2010;Archer, Oscar-Berman, Blum, & Gold, 2012;Palomo, Beninger, Kostrzewa, & Archer, 2008a, b).…”
Section: Hypothesized Cultural Aspects: Main Effectsmentioning
confidence: 99%
“…A large volume of empirical studies have been carried out to investigate the relationships between adolescents' friendship networks and various cognitive, psychological and behavioural variables, such as academic achievement (e.g., Goza & Ryabov, 2009;Riegle-Crumb & Callahan, 2009), aggressive behaviours (e.g., Rose et al, 2004), substance and drug use (e.g., Kramer & Vaquera, 2011;Pilkington & Sharifullina, 2011), sexual activities (e.g., Udry & Billy, 1987), and schoolto-work transition (e.g., Sletten, 2011). The measurement of the adolescent friendship networks in these studies have been inconsistent, therefore, the scale developed in this study could be a useful tool to assist the investigation in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Franklin Goza and Igor Ryabov (2009) found that coethnic friendships can be beneficial for one's academic achievement, especially for Asian Americans, suggesting that value of coethnic ties is dependent on the specific ethnic group and the available resources. Franklin Goza and Igor Ryabov (2009) found that coethnic friendships can be beneficial for one's academic achievement, especially for Asian Americans, suggesting that value of coethnic ties is dependent on the specific ethnic group and the available resources.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Indeed, ethnic intermarriage is often understood as both the outcome and harbinger of social openness (Kalmijn 1998;Qian and Lichter 2007) and may lead to a social network containing more native contacts via preferences, opportunities, and more openness of natives toward mixed than toward immigrant couples. It has been suggested that native-born friends can help diffuse norms of acceptable behavior (Coleman et al 1966), give access to social and economic resources, and offer the cultural resources that provide means of self-presentation and patterns of communication that are valued in the majority context of the school (Goza and Ryabov 2009;Ward, Bochner, and Furnham 2001). their knowledge of the host culture and language) to establish a social network with ethnically cross-cutting ties themselves.…”
Section: Structural Characteristicsmentioning
confidence: 99%